N-acetylcysteine use in a cocaine-induced liver failure: a case report - Vanessa Biering; Ronan Bellouard; Ronan Bellouard; Maëlle Martin; Éric Dailly; Éric Dailly; Catherine Monteil-Ganière; Edouard Charles Le Carpentier (Frontiers in Toxicology)
BackgroundCocaine intoxication and abuse is a worldwide problem that can be the cause of numerous acute medical complications, including severe acute hepatitis. Although these cases are scarce, they are extremely serious and may lead to liver transplantation or death. Management of toxic hepatitis, once the causative agent has been discontinued, is essentially symptomatic, based on clinical and biological monitoring and prevention of complications related to acute hepatitis.Case detailsWe present a case of a 28-year-old woman admitted to the emergency department for acute hepatitis due to cocaine intoxication. In addition to a sharp rise in her liver enzymes, the patient also presented metabolic acidosis, renal failure, and rhabdomyolysis. Treatment consisted of administering N-acetylcysteine (NAC), dialysis, and additional supportive measures. An improvement in the liver function with a decrease in transaminases occurred after the NAC administration. The toxicokinetics of major cocaine metabolites and clinical chemistry concentrations were monitored.ConclusionIn addition to the usual management measures for acute hepatitis, the administration of N-acetylcysteine should be investigated further, although it is currently used only in cases of acetaminophen acute toxic hepatitis.